Determinants of financial performance: reviewed from financial structure and dividend policy - Rahman, Karlina Ghazalah; Rahman, Moch Ridho Ghazali; Mus, Abdul Rahman (Institute of Computer Science (IOCS), 2024)
This study was conducted to analyze the relationship between financial structure and dividend policy on financial performance. The grand theories used are trade-off theory and dividend irrelevance theory. The research method used is quantitative with a causal analysis approach. This study used secondary data with a purposive sampling method, the sample of this study was 32 companies with the amount of data observed as many as 128 data. The results of this study show that: (1) Financial structure has a positive and significant effect on the company's financial performance; (2) Dividend policy has a negative and significant effect on the company's financial performance.